노인들의 건강문제와 컴퓨터 게임 요구도의 상관성 분석 - 임경춘(Kyung-Choon Lim); 이윤정(Yoon-Jung Lee); 안준희(Joonhee Ahn) (한국콘텐츠학회 논문지, 9(11), 2009)
Regular activity program is needed for managing chronic disease and obesity and preventing falls as a nursing intervention. It seems that serious game will be very important for older people to keep them active with fun to improve their health. This study was conducted to explore the correlations between health problems and computer game needs in the elderly. This was a cross-sectional study. A questionnaire was developed and administered to a convenience sample of adults who are older than 55 years, recruited from several places through trained research assistants and research center that has online pools in Korea. 778 subjects (mean age: $61.4\;{±}\;5.6$) were participated in this study. The majority of subjects was male (68.6%). We found that there was higher needs for exercise or serious game in the group of ma1e(55.4%), below undergraduate(66.2%), under two family members(32.5%), over 350,000 won of pocket money/month (40.1%), mild depressive symptom (51.7%), and online responser(68%). Especially, they wanted to overcome physical limitations through games. Higher education, more experiences and skills of using computer/internet was statistically and positively significant to the needs for exercise or serious game. In conclusion, there exists a potential market within this demographic group for the use of serious games. Thus, we need to develop senior games in Korean to improve quality of life and health promotion. 만성질환 및 비만 관리와 낙상예방 등을 위한 간호중재의 하나로 규칙적인 신체활동의 필요성이 대두되고 있는데, 운동게임 등의 기능성 게임을 질병예방 교육과 치료보조, 재활 등에 응용하는 방안은 점차 중요영역이 될 것으로 보인다. 본 연구는 건강문제와 컴퓨터 게임요구도의 상관관계를 알아보기 위해 설문지를 이용하여 실시한 횡단적 조사 연구이다. 훈련된 연구보조원들의 면접조사와 전문조사기관의 온라인조사 결과 778명(평균 연령: $61.4\;{±}\;5.6$)의 대상자가 참여하였는데, 그 중 68.6%가 남자였다. 분석결과 남성(55.4%), 고졸이하(66.2%), 2명 이하의 가족수(32.5%), 월평균 35만원 이상(40.1%), 경증 우울증(51.7%), 온라인 응답자(68%) 그룹에서 게임 요구도가 높게 나타났다. 특히 게임을 통해 신체적 제약을 극복하고 싶어했다. 상관성 분석에서는 교육수준이 높을수록, 컴퓨터 이용 경험이 있을수록, 컴퓨터/인터넷 활용이 능숙할수록 운동게임이나 기능성 게임에 대한 요구도가 높았다. 결론적으로, 노인그룹을 위한 여가활용 차원에서의 즐거움과 건강증진의 효과를 모두 가져올 수 있는 노인용 기능성 게임이 개발된다면 노인의 건강증진과 삶의 질 향상에 크게 기여하리라 사료된다.